Isolation technology and process for extracting Ni and Co from nickel-containing high-cobalt hydroxide - WANG RUILIN; YANG YONGNING; ZHAO MINGYU; WU YUMING; ZHOU TONG; DING CAISHENG; ZHANG JUN; GENG WENJIE; WEI XIULAN; LI QUAN; ZHAO LIPING; YOU GUANGHONG (2016)
The sulfuric acid total leaching process is adopted in an isolation technology and process for extracting nickel and cobalt from nickel-containing high-cobalt hydroxide, so that a high Ni and Co leaching rate is guaranteed. By means of the processes of sulfuric acid leaching, impurity removal, extraction, and Ni-Co isolation, leaching agents rich in metallic nickel and metallic cobalt are obtained, the leaching agents are directly fed into an electro-deposited nickel and electro-deposited cobalt production system, and accordingly metallic nickel and metallic cobalt are isolated and extracted. The obtained leaching agents rich in metallic nickel and metallic cobalt can directly enter the electro-deposited nickel and electro-deposited cobalt production system. In addition, the process for extracting nickel and cobalt from nickel-containing high-cobalt hydroxide is simple, efficient, environment-friendly and suitable for treating nickel-containing high-cobalt hydroxide.